Karakteristik Pemerintah Daerah, Opini dan Ketepatwaktuan Laporan Keuangan di Indonesia - Okfitasari, Antin; Sundari, Sundari; Meikhati, Ety (ITB AAS INDONESIA, 2020)
This research is aimed to examine the impact of local governmental characteristics and audit opinion on the timeliness of local governmental financial statement. The characteristics of local governmental will be measured by using the size of the area, regional wealth (PAD), status and governmental spending. All of the samples are 453 City across Indonesia that has profile report as regulated by BPK database. The results showed the size of local governmental had positive effect totimeliness but the governmental revenue had negative effect. The others variables, governmental status, governmental spending and audit opinion, had no significant effect to timeliness